Development of a novel SiO2 based composite anode material for Li-ion batteries. (2017) - Babaa, M.R.; Moldabayeva, A.; Karim, M.; Zhexembekova, A.; Zhang, Y.; Bakenov, Z.; Molkenova, A.; Taniguchi, I.
Abstract: Research interest towards Li-ion batteries (LIBs) has been significantly increased over decades as high power energy storage systems for renewable energy generators and electrical vehicles emerged. One of the most representative anode materials for LIBs is silica (SiO2 ) thanks to its high theoretical capacity of 1965 mAh·g -1 . However, low coulombic efficiency and irreversible capacity losses during cycling of silica-based anodes are critical issues that need to be addressed nowadays. In this work, a novel three-dimensional SiO2 /carbon nanotube/graphene ternary composite was developed as an anode material for LIBs to improve electrochemical performances and to make significant advances as a potential candidate for high-energy applications. The novel ternary composite with weight ratio of 50:25:25 exhibited initial discharge and charge capacities of 732 mAh·g -1 and 260 mAh·g -1 respectively, with initial coulombic efficiency of 82%. Nevertheless, further investigations are necessary for attaining higher specific capacities, enhanced cyclic stability and better rate capability.